2006
DOI: 10.1002/ijc.21855
|View full text |Cite
|
Sign up to set email alerts
|

Trends in laryngeal cancer mortality in Europe

Abstract: After a steady increase since the 1950s, laryngeal cancer mortality had tended to level off since the early 1980s in men from most European countries. To update trends in laryngeal cancer mortality in Europe, age‐standardized (world standard) mortality rates per 100,000 were derived from the WHO mortality database for 33 European countries over the period 1980–2001. Jointpoint analysis was used to identify significant changes in mortality rates. In the European Union (EU) as a whole, male mortality declined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
49
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 27 publications
4
49
0
1
Order By: Relevance
“…The importance of tobacco and alcohol on laryngeal cancer mortality is also reflected by the similarity of trends to those for lung cancer 27,28 and other tobacco-and alcohol-related neoplasms. 29 Moreover, as reported in a few other studies, 20,[30][31][32] over the last few decades declines were also observed in laryngeal cancer incidence, influenced by changes in risk factors exposures only, in the absence of populations programs of screening for the disease. Thus, the steady decrease and the changes in tobacco use in subsequent generations of European men largely explains the fall in male laryngeal cancer mortality in several countries, particularly in middle-age.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…The importance of tobacco and alcohol on laryngeal cancer mortality is also reflected by the similarity of trends to those for lung cancer 27,28 and other tobacco-and alcohol-related neoplasms. 29 Moreover, as reported in a few other studies, 20,[30][31][32] over the last few decades declines were also observed in laryngeal cancer incidence, influenced by changes in risk factors exposures only, in the absence of populations programs of screening for the disease. Thus, the steady decrease and the changes in tobacco use in subsequent generations of European men largely explains the fall in male laryngeal cancer mortality in several countries, particularly in middle-age.…”
Section: Discussionmentioning
confidence: 70%
“…In contrast, alcohol drinking prevalence has been increasing at least up to more recent years in countries of central and eastern Europe. 33,36 Such countries have now the highest laryngeal mortality rates on a European scale, and the control of laryngeal cancer-as well as of other tobacco and alcohol-related cancers 29 -remains a major public health problem in these areas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations